2010
DOI: 10.1111/j.1600-0501.2010.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, controlled clinical trial evaluating the clinical and radiological outcome after 3 years of immediately placed implants in sockets exhibiting periapical pathology

Abstract: Abstract:Objectives: The aim of the present study was to compare the clinical and radiological outcome of immediately placed implants in sockets with or without periapical pathology 3 years after implant placement. Materials and methods:29 patients with immediate implant placement were clinically and radiologically followed 3 years after implant placement (test-group: 16 patients without periapical pathology, control-group: 13 patients with periapical pathologies). Clinical (FMBS, FMPS, CAL, width of keratiniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 20 publications
2
86
0
6
Order By: Relevance
“…Moreover, many studies have reported an increase in loss of endosseous implants at sites associated with periodontal disease 12,24,35) , whereas few have reported satisfactory results 13,20) . Similar success rates have been reported, however, with immediate implant placement whether the site was infected or not, provided infection was controlled thorough debridement of alveolar tissue by curettage and administration of broad-spectrum antibiotics 17,20,31,32,50,55) .…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…Moreover, many studies have reported an increase in loss of endosseous implants at sites associated with periodontal disease 12,24,35) , whereas few have reported satisfactory results 13,20) . Similar success rates have been reported, however, with immediate implant placement whether the site was infected or not, provided infection was controlled thorough debridement of alveolar tissue by curettage and administration of broad-spectrum antibiotics 17,20,31,32,50,55) .…”
Section: Introductionmentioning
confidence: 49%
“…Hence, the presence of periapical infection should not be considered as a potential contraindication for immediate implant placement. Furthermore, human clinical studies have reported that implant survival rate ranged from 92 to 100% after 12 to 60 months of follow-up 13,17,20,31,32,50,55) . One study reported that the implant survival rate was 100%, and that hard and soft tissue integration was similar and favorable between the healthy and infected groups 18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El empleo de Bio-Oss® , utilizado en este caso clínico, como biomaterial de relleno en defectos óseos, periodontales e implantológicos, ha demostrado una gran eficacia clínica en el tratamiento con implantes, siendo importante a la hora de evitar en lo posible, el proceso de reabsorción ósea del alvéolo postextracción que va intrínsecamente unido a la cicatrización postexodoncia (31)(32)(33). Este material, debe utilizarse, en un favorable "ambiente osteogénico", situándolo sobre un lecho receptor que favorezca la revascularización rápida del material injertado y con la mayor estabilidad posible, en función del material utilizado, morfología y tamaño del defecto, así como la técnica que finalmente se haya decidido emplear (34,35).…”
Section: Discussionunclassified
“…(1) Estudos clínicos têm demonstrado que a taxa de sucesso dos implantes imediatos é similar a dos implantes instalados após o reparo ósseo. (2)(3)(4)(5) Evidências científicas demonstram que a implantação imediata preserva a arquitetura alveolar e favorece a manutenção da altura das cristas ósseas, (6,7) assim, a manutenção do contorno e da espessura gengival é favorecida, fatores essenciais para uma ção do longo eixo do cabo em relação a raiz dentá-ria (Figura 3, Apêndice A).…”
Section: Introductionunclassified